Changes in Survival Outcomes of Patients With Neuroendocrine Neoplasms Over the Past 15 Years: A Real-World Study. (6th May 2022) - Abdel-Rahman, Omar; Pham, Truong-Minh; Pokhrel, Arun; Ruether, Dean; Sawyer, Michael B.
Abstract : Background: The past 2 decades have observed a number of advances in therapeutic approaches to patients with neuroendocrine neoplasms (NENs). This study aims to assess whether survival outcomes have changed among patients with NENs over the past 15 years, in a real-world, population-based study. Materials and Methods: We accessed administrative databases within the province of Alberta, Canada, and we reviewed patients with invasive NENs diagnosed 2004 to 2019. Patients were classified according to the year of diagnosis into 3 groups: 2004 to 2008; 2009 to 2013; and 2014 to 2019. Kaplan-Meier survival estimates were used to compare overall survival (OS) according to different baseline characteristics (including the year of diagnosis). Multivariable Cox regression modeling was used to examine factors associated with the risk of death in this cohort. Results: We included a total of 3431 patients in the study cohort. Using multivariable Cox regression analysis, the following factors were associated with worse survival: older age at diagnosis (hazard ratio [HR]: 3.45; 95% CI [confidence interval]: 2.74-4.35), male sex (HR: 1.38; 95% CI: 1.21-1.56), lung primary site (HR for lung vs. appendicular primary: 1.39; 95% CI: 1.01-1.92), Stage 4 disease (HR: 2.80; 95% CI: 2.38-3.30), South zone of the province (HR for South zone vs. Calgary zone: 1.85; 95% CI: 1.49-2.30), and higher comorbidity index (HR for ≥3 vs. 0: 2.66; 95% CI: 2.19-3.24). Although Kaplan-Meier method showed significant difference in OS according to diagnosis period, multivariable regression model showed that the period of diagnosis did not appear to impact OS (HR for diagnosis period 2004 to 2009 vs. 2014 to 2019: 1.04; 95% CI: 0.89-1.22). Conclusions: Over the study period (2004 to 2019), patients diagnosed during later periods did not appear to experience better OS compared with patients diagnosed at an earlier time.